The Effect of de-Sitter Like Background on Increasing the Zero Point Budget of Dark Energy - Haidar Sheikhahmadi; Ali Aghamohammadi; Khaled Saaidi (Advances in High Energy Physics)
During this work, using subtraction renormalization mechanism, zero point quantum fluctuations for bosonic scalar fields in a de-Sitter like background are investigated. By virtue of the observed value for spectral index, ns(k), for massive scalar field the best value for the first slow roll parameter, ϵ, is achieved. In addition, the energy density of vacuum quantum fluctuations for massless scalar field is obtained. The effects of these fluctuations on other components of the universe are studied. By solving the conservation equation, for some different examples, the energy density for different components of the universe is obtained. In the case which all components of the universe are in an interaction, the different dissipation functions, Q~i, are considered. The time evolution of ρDE(z)/ρcri(z) shows that Q~=3γH(t)ρm has the best agreement in comparison to observational data including CMB, BAO, and SNeIa data set.